Noncontrast-enhanced magnetic resonance renal angiography using a repetitive artery and venous labelling technique at 3 T: comparison with contrast-enhanced magnetic resonance angiography in subjects with normal renal function - Park, Sung Yoon; Kim, Chan Kyo; Kim, EunJu; Park, Byung Kwan (European radiology, 2015)
Objectives To investigate the feasibility of noncontrast-enhanced MR angiography (NC-MRA) using the repetitive artery and venous labelling (RAVEL) technique to evaluate renal arteries compared to contrast-enhanced MR angiography (CE-MRA). Methods Twenty-five subjects with normal renal function underwent NC-MRA using a RAVEL technique and CE-MRA at 3 T. Two independent readers analysed the MRA images. Image quality, number of renal arteries, presence or absence of an early branching vessel, and diameter of the main renal arteries were evaluated. Results The overall image quality of NC-MRA was fair or greater in 88 % of right and 92 % of left renal arteries, while it was 96 % in both sides with CE-MRA. On NC-MRA, the number of renal arteries in all subjects was perfectly predicted by both readers. Sensitivity and specificity for predicting early branching vessels were 82 % and 100 % for reader 1 and 82 % and 95 % for reader 2. Inter-modality agreement for comparing the diameters of main renal arteries was good or excellent at all segments for both readers. Inter-reader agreement was moderate or good at all segments except at the right distal segment on NC-MRA. Conclusion NC-MRA with the RAVEL technique at 3 T may have comparable diagnostic feasibility for evaluating renal arteries compared to CE-MRA. Key Points • Accurate pre - treatment evaluation of renal artery anatomy helps clinical decision - making . • NC - MRA using RAVEL offers acceptable imaging quality for renal artery evaluation . • The 3 T RAVEL technique provides excellent diagnostic performance for renal artery evaluation . • The 3 T RAVEL technique may be an alternative to contrast - enhanced MRA .